Effectiveness of Vitamin C Supplementation in Periodontal Therapy - Rafisa, Anggun; Sovira, Gita Dwi Jiwanda (Sean Institute, 2025)
Periodontal disease is a chronic inflammatory condition initiated by microbial dysbiosis and driven by host immune responses, notably the overproduction of reactive oxygen species (ROS), which contribute to tissue damage. Vitamin C (ascorbic acid), a potent antioxidant, plays a role in collagen synthesis and immune regulation. Several studies have proposed vitamin C as an adjunct in periodontal therapy, yet its effectiveness remains unclear. This systematic review aims to evaluate the effect of vitamin C supplementation on clinical periodontal parameters in patients with periodontal disease. A comprehensive literature search was conducted in PubMed and Scopus for randomized controlled trials (RCTs) published between January 2015 and June 2025. Included studies investigated vitamin C supplementation in patients with periodontal disease without systemic conditions, pregnancy, lactation, or medication use. Studies involving vitamin C in combination with other nutrients without a separate vitamin C-only group were excluded. Data extraction and analysis followed the PRISMA guidelines. Four RCTs met the inclusion criteria. Significant clinical improvements were observed in periodontal parameters following non-surgical periodontal therapy (NSPT). However, the addition of vitamin C supplementation alone did not consistently provide significant improvements beyond NSPT alone. One study showed greater improvements when vitamin C was combined with melatonin, and another suggested potential benefits from guava—a natural source of vitamin C and polyphenols—over synthetic vitamin C. Current evidence suggests that while vitamin C supplementation may offer modest anti-inflammatory and antioxidant benefits, it does not consistently enhance clinical outcomes in periodontal therapy when used alone.